Facial Adiposity, Attractiveness, and Health: A Review - de Jager, Stefan; Coetzee, Nicoleen; Coetzee, Vinet (Frontiers in Psychology, 2018)
The relationship between facial cues and perceptions of health and attractiveness in others plays an influential role in our social interactions and mating behaviors. Several facial cues have historically been investigated in this regard, with facial adiposity being the newest addition. Evidence is mounting that a robust link exists between facial adiposity and attractiveness, as well as perceived health. Facial adiposity has also been linked to various health outcomes such as cardiovascular disease, respiratory disease, blood pressure, immune function, diabetes, arthritis, oxidative stress, hormones and mental health. Though recent advances in the analysis of facial morphology has led to significant strides in the description and quantification of facial cues, it is becoming increasingly clear that there is a great deal of nuance in the way that humans use and integrate facial cues to form coherent social or health judgments of others. This paper serves as a review of the current literature on the relationship between facial adiposity, attractiveness, and health. A key component in utilizing facial adiposity as a cue to health and attractiveness perceptions is that people need to be able to estimate body mass from facial cues. To estimate the strength of the relationship between perceived facial adiposity and body mass, a meta-analysis was conducted on studies that quantified the relationship between perceived facial adiposity and BMI/percentage body fat. Summary effect size estimates indicate that participants could reliably estimate BMI from facial cues alone (r = 0.71, n = 458).